(untitled) (Global Journal of Science Frontier Research, 2017)
This paper investigated the roughness of NASA Stage 35 test compressor. Surface roughness can change the geometric line in the microcosm, which causes the compressor operation to deviate from the design point under working conditions. Wall function was used in this study to describe roughness. Roughness calculation model in nonuniform distribution was established along the chord and spanwise directions. Basing on certain rules, rotor blades were attached with roughness to determine the influence of blade roughness position distribution on the overall performance of the compressor and internal flow. Results show that when roughness was distributed from the blade leading edge to 40% of the chord, the compressor performance was greatly influenced; in severe performance, compressor efficiency decreased by more than 2%. Roughness position distribution in blade height direction exhibited a minimal effect on the entire compressor performance, which can be ignored.